2021
DOI: 10.1002/admt.202100572
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Based Nanomaterials and Sensing Tools for Wearable Health Monitoring Devices

Abstract: In this manner, sensor technologies have garnered great attention in various fields, including biomedicine, [2][3][4][5] environmental monitoring, [6][7][8][9] smart devices, [10] wearable devices, [11] automobile manufacturing [12] since the semiconductor materials and circuits have been developed. In particular, biosensors are powerful and innovative analytical tools that incorporate biological receptors to recognize biological analytes through either physical or chemical transducers. Primarily, bio-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 364 publications
(370 reference statements)
0
33
0
Order By: Relevance
“…However, only a small volume of samples can be processed with this method, and contamination would notably interfere with their efficiency. , Size-exclusion chromatography usually impedes with prolonged assay time, limited sample volume, and the contamination of similar size particles . Although precipitation-based strategies utilizing polymeric substances hold significant impact in the field, interfering participation agents, molecular assembly/membrane fusion of particles, and coprecipitation of the other particles are still obstacles for this method. , On the other hand, immunoaffinity-based alternatives result in low-yield; highly rely on the antibody quality; and require other integrative systems such as sensor platforms or sophisticated cell counters, hence increasing their cost and hindering their utility in broader applications. , …”
Section: Discussionmentioning
confidence: 99%
“…However, only a small volume of samples can be processed with this method, and contamination would notably interfere with their efficiency. , Size-exclusion chromatography usually impedes with prolonged assay time, limited sample volume, and the contamination of similar size particles . Although precipitation-based strategies utilizing polymeric substances hold significant impact in the field, interfering participation agents, molecular assembly/membrane fusion of particles, and coprecipitation of the other particles are still obstacles for this method. , On the other hand, immunoaffinity-based alternatives result in low-yield; highly rely on the antibody quality; and require other integrative systems such as sensor platforms or sophisticated cell counters, hence increasing their cost and hindering their utility in broader applications. , …”
Section: Discussionmentioning
confidence: 99%
“…Briefly, smart materials, including aerogel-based polymers, bioconjugates, nanofibers, metal foams, piezoelectric materials, and shape-memory materials, have been utilized in diagnostic devices for this manner. [79][80][81] For example, graphene-a conductive and 2D smart material with a very long periodic carbon honeycomb chain in the horizontal plane [82] -was integrated into a platform to identify and enrich CTCs/CTM as high as 98.15% of efficiency thanks to its high conductance ability. [80] The most widely used physical approaches for the isolation and enrichment of these tumor cells involve size and deformability-based filtration, [71,83] density-gradient centrifugation, [84] and electrical property-based dielectrophoresis (DEP) separation.…”
Section: Clinical/research Methods For Ctcs/ctm Enrichment and Isolationmentioning
confidence: 99%
“…Besides, thanks to the unique properties of carbon composite materials, temperature sensors have been widely proposed on the basis of these composites. [60,186] These temperature sensors are characterized by the fact that resistance can decrease (based on a negative temperature coefficient) or increase (based on a positive temperature coefficient) with the increasing temperature. Kim et al reported highly flexible and sensitive temperature sensors based on aligned carbon nanofiber (ACNF) films (Figure 11f).…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%